Digitalisasi Manajemen Operasional sebagai Upaya Peningkatan Daya Saing UMKM Batik TIN - Siswohadi Siswohadi; Shafira Aulia Rahma (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2026)
This study aims to analyze the implementation of digitalization in the operational management of Batik TIN MSMEs as a strategy to enhance business competitiveness. Digitalization is considered an important step for MSMEs in facing increasingly competitive market conditions in the digital economy era. The research method employed is qualitative with a case study approach. Data were collected through in-depth interviews with the owner and employees of Batik TIN MSMEs, direct observation of operational processes, and documentation related to production, marketing, and financial management activities. The results show that the implementation of digitalization in the production aspect helps improve work efficiency and product quality control. In the marketing aspect, the utilization of social media and digital platforms is able to expand market reach and enhance interaction with consumers. Meanwhile, digitalization in financial management facilitates transaction recording, improves the accuracy of financial reports, and supports more accurate decision-making. Overall, the implementation of digitalization has proven to make a positive contribution to improving operational efficiency and strengthening the competitiveness of Batik TIN MSMEs. Therefore, digitalization can be an effective and sustainable strategy for MSMEs to survive and grow amid dynamic industrial competition.